Mediation effect of psychological contract between personality dimensions and turnover intention - Maryam Saeed (Journal of Economics, Finance and Administrative Science, 2020)
Purpose - This study aims to test the mediating role of psychological contract (PC) in a relationship between personality dimensions and turnover intention. Design/methodology/approach - The current study is analytical in nature. The data for the purpose of the analysis is collected from 300 software engineers working in Lahore, Punjab. Purposive sampling technique is used for the collection of this data. The response rate was 87.33 per cent. Different data analysis techniques such as correlation, regression analysis, are used to test the 10 hypotheses of the study. Moreover, the study adopted a cross-sectional survey design. Findings - According to regression analysis, extroversion, conscientiousness and agreeableness personality dimensions brought positive but insignificant increments in turnover intention. However, emotionally stable personality dimensions brought positive and significant increments in turnover intention. Open to experience personality dimension brought negative but insignificant decrement in turnover intention. Results showed extroversion personality dimension brought a very less but insignificant increment in variations of PC, which have higher contributions in variations of turnover intention. Emotional stable, conscientiousness and agreeableness personality dimensions brought also very less but a significant increment in PC. Open to experience personality dimension have negative but insignificant decrement in PC. Results showed the mediation impact of PC among emotional stability, conscientiousness and agreeableness personality dimensions and turnover intention. However, PC does not mediate among extroversion, open to experience personality dimensions and turnover intention. The paper concludes with recommendations for further research. Originality/value - This study will help the organization in reducing the turnover rate and can enhance the motivation level of their employees.
Keywords: J31; M54; 330; Agreeable personality dimension (APD); Consciousness personality dimension (CPD); Extroversion personality dimension (EPD); Openness to experience personality dimension (OEPD); Psychological contract (PC)